Work Life Balance For Lecturers at IAIN Kerinci and Its Impact On Tridharma Productivity - Yani, Ahmad; Havidz Aima, M. (International Journal of Advanced Multidisciplinary, 2024)
Lecturers often face unique challenges in maintaining a balance between work and personal life due to the nature of their profession. Therefore, lecturers at IAIN Kerinci require work-life balance to fulfill their duties effectively. This study aims to identify aspects related to work-life balance among lecturers at IAIN Kerinci and strategies that institutional management can implement to sustain this balance. The research employs a Systematic Literature Review (SLR) method using the PRISMA pattern. Findings highlight several aspects linked to lecturer work-life balance, including: 1) time allocation between work and family, 2) workload and commitments, 3) dual roles as lecturers and family members, 4) resilience in fulfilling tridharma responsibilities, and 5) job satisfaction. Human resource management implications include scheduling considerations, adequate rest periods, and access to physical and mental health resources, especially for lecturers' families.